2007
DOI: 10.1002/eat.20448
|View full text |Cite
|
Sign up to set email alerts
|

Stability of eating disorder diagnoses: A commentary

Abstract: Eat ing disorders, including anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder (BED), are one of the most prevalent psychiatric problems for girls and young women, result in subjective distress and functional impairment, and increase risk for future onset of obesity, depression, suicide attempts, anxiety disorders, substance abuse, and health problems. 1,2 Although these eating disorders are clearly associated with functional impairment, less is known about the course of these eating disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In addition, they had more severe bulimic symptoms at the beginning of the treatment (higher initial scores in the BITE and the PSRs) and a greater tendency to present a lack of response after 6 months of treatment (29% of BN/AN1 patients vs. 6% of BN/AN2 did not respond). Although some authors have pointed out that it is not the diagnosis but low body weight or longer duration of more severe eating disorder which are related to worse outcome, 34,35 our findings support the idea that a history of AN in BN patients can be a factor associated to a protracted illness. In conclusion, our Study #1 replicates the data reported in literature, which defend the existence of differences between BN patients with/without a history of AN.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, they had more severe bulimic symptoms at the beginning of the treatment (higher initial scores in the BITE and the PSRs) and a greater tendency to present a lack of response after 6 months of treatment (29% of BN/AN1 patients vs. 6% of BN/AN2 did not respond). Although some authors have pointed out that it is not the diagnosis but low body weight or longer duration of more severe eating disorder which are related to worse outcome, 34,35 our findings support the idea that a history of AN in BN patients can be a factor associated to a protracted illness. In conclusion, our Study #1 replicates the data reported in literature, which defend the existence of differences between BN patients with/without a history of AN.…”
Section: Discussionsupporting
confidence: 84%
“…It is also possible that impulsivity, which was higher in our BN/AN1 R patients than in our BN/AN1 BP patients, might be related to the poorer outcome observed in the former, as it has been widely demonstrated that impulsivity is a strong predictor of bad outcome in BN 12,34,[43][44][45][46][47][48] In conclusion, it has been suggested that studies should be designed to determine whether the diagnosis of AN or certain aspects of AN may be capable of determining clinical characteristics or outcome in patients with BN. 35 Our study should be considered a modest contribution to this line of thinking. We have considered the subtype of previous AN as a differential criterion which could be of interest in order to subtype patients with BN.…”
Section: Discussionmentioning
confidence: 94%
“…A second strength is that we investigated ED symptoms instead of ED diagnoses, as it was already recommended by Stice and Spoor. 43 Next, the use of structured clinical interviews to assess eating-disordered behaviors was another important asset of this study. A final strength was the inclusion of a sample that consisted of both boys and girls.…”
Section: Discussionmentioning
confidence: 99%